2016
DOI: 10.1080/15389588.2015.1120296
|View full text |Cite
|
Sign up to set email alerts
|

Ankle fracture patterns in drivers are associated with femoral fracture, higher BMI, and advanced age

Abstract: Efforts to reduce the risk of driver ankle injury should focus on right foot and pedal interaction. The range of injury patterns identified here suggest that efforts to minimize driver ankle fracture risk will likely need to consider injury tolerances for flexion, pronation/supination, and axial loading in order to capture the full range of injury mechanisms. In the clinical environment, physicians examining drivers after a frontal crash should consider those who are older or obese or who have severe femoral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Some studies show that BMI is related to osteoporotic fracture risk. [15][16][17] The results of previous research suggested that low BMI (<20kg/m 2 ) should go for a DXA in women less than 60-year-old. 18 The results of many studies have suggested a correlation between BMI and BMD in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show that BMI is related to osteoporotic fracture risk. [15][16][17] The results of previous research suggested that low BMI (<20kg/m 2 ) should go for a DXA in women less than 60-year-old. 18 The results of many studies have suggested a correlation between BMI and BMD in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%